ANALISA PERENCANAAN DAN PENGEMBANGAN TERHADAP PENGELOLAAN BUMDES ALAMIN DESA BAGAN JAYA KECAMATAN ENOK - Hamzah_Hamzah; Edi Susanto (AMNESIA (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2023)
This research aims to see the influence of planning and development on the management of Bumdes Alamin, Bagan Jaya Village, Enok District. Transmigration number 4 of 2015 which states that villages can establish village-owned enterprises called BUMDES Village government can establish village-owned enterprises in accordance with the needs and potential of the village with the hope of increasing village income and the welfare of village communities Law no. 23 of 2004. Data collection used is in the form of interviews and distributing questionnaires. Implementation of BUMDes program management to increase community income by providing capital loans and providing training to the community as members of Bumdes Alamin. Based on the questionnaire results, it shows that Bumdes Alamin has carried out planning and development to improve the management of Bumdes very well in accordance with the procedures and rules set by the Bagan Jaya village government, Enok sub-district.